Retailing - Dunne, Patrick M. (Thomson/South-Western, 2008)
This market-leading text gets stronger with each new edition. Written by retail authorities Dunne and Lusch, the sixth edition of RETAILING delivers the book's signature in-depth, cutting-edge coverage of the latest trends and practices in the fast-paced retail market. Packed with real-world examples and behind-the-scenes coverage, the book captures the excitement of the high-energy retail trade. Special emphasis is given to the impact of the Internet as well as the continuing changes in the world's economic systems. Endorsed by the National Retailing Federation, RETAILING features a conversational writing style and a vibrant full-color format in a succinct 14 chapters, which can easily be covered in one term. Seasoned instructors, Dunne and Lusch believe that case studies are critical in helping students understand the intricacies of retail management. Giving students hands-on experience putting chapter concepts into action, the book includes a built-in study guide with countless practical applications, including review questions, writing and speaking exercises, cases covering the gamut of retail operations, a computer spreadsheet case involving a small retail shop, and more